SERCAP: is the perfect the enemy of the good? - White, NJ; Nosten, FH (BioMed Central, 2021)
Single Encounter Radical Cure and Prophylaxis (SERCAP) describes an ideal anti-malarial drug that cures all malaria in a single dose. This target product profile has dominated anti-malarial drug discovery and development over the past decade. The operational advantage of a single encounter has to be balanced against the need for a high dose, reliable absorption, little variability in pharmacokinetic properties, slow elimination (to ensure curative drug exposures in all patients) and a very low rate of vomiting. The demanding aspirational target may have hindered anti-malarial drug development. Aiming for three-day regimens, as in current anti-malarial treatments, would be better.